2013
DOI: 10.1021/es4000356
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Surface Sampling for Bacillus Spores Using Commercially Available Cleaning Robots

Abstract: Five commercially available domestic cleaning robots were evaluated on their effectiveness for sampling aerosol-deposited Bacillus atrophaeus spores on different indoor material surfaces. The five robots tested include three vacuum types (R1, R2, and R3), one wet wipe (R4), and one wet vacuum (R5). Tests were conducted on two different surface types (carpet and laminate) with 10(6) colony forming units of B. atrophaeus spores deposited per coupon (35.5 cm × 35.5 cm). Spores were deposited on the center surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…3C). Even though the relative recovery efficiency associated with carpet was significantly lower than that with other surfaces, the total yield was consistent with previously published reports (18,29,30). Lastly, considering the extraction buffer volume and reliable counting standard, the liquid extraction with CFU plating had a limit of detection (LOD) of 100 CFU/ coupon, which was confirmed by performing liquid deposition LOD experiments for all four surfaces (Fig.…”
Section: Methods Development-bacterial Extraction and Enumerationsupporting
confidence: 90%
See 1 more Smart Citation
“…3C). Even though the relative recovery efficiency associated with carpet was significantly lower than that with other surfaces, the total yield was consistent with previously published reports (18,29,30). Lastly, considering the extraction buffer volume and reliable counting standard, the liquid extraction with CFU plating had a limit of detection (LOD) of 100 CFU/ coupon, which was confirmed by performing liquid deposition LOD experiments for all four surfaces (Fig.…”
Section: Methods Development-bacterial Extraction and Enumerationsupporting
confidence: 90%
“…In 2008, Sinclair et al published an extensive review of all previous studies evaluating the environmental stability of several infectious agents, both bacterial and viral, on indoor and outdoor surfaces utilizing either liquid or aerosol deposition (13). Most of the studies utilized liquid deposition of agent onto coupons rather than aerosol deposition to evaluate agent stability, which does not mimic a deposition of respirable aerosol particles onto surfaces (1,(14)(15)(16)(17)(18). In addition, the majority of surface stability studies have focused on enteric pathogens in food protection studies (15,(19)(20)(21)(22).…”
mentioning
confidence: 99%
“…If the carpet in our study had been sampled using the vacuum‐based method, the collection efficiencies of the robots in comparison would have increased by a factor of 10 3 , giving a recovery percentage closer to that seen by Lee et al . ().…”
Section: Discussionmentioning
confidence: 97%
“…The Lee et al study derived its results by comparing robot results to the recovery from surface sampling, in a similar way to this study; however Lee et al used a vacuumbased method for recovering from carpet, whereas we employed a water-soluble tape method. (Lee et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Such an advantage may be desirable when collecting vast numbers of samples, such as during characterization sampling following a wide-area incident (Buttner et al, 2004; Franco and Bouri, 2010; Schmitt and Zacchia, 2012). It has been suggested that using robotic sampler to generate composite samples could decrease the amount of effort expended by both sample collection teams and analysis laboratories (Lee et al, 2013). …”
Section: Discussionmentioning
confidence: 99%